Seasonal watershed-scale influences on nitrogen concentrations across the Upper Mississippi River basin. Issue 2 (25th January 2022) - Wine, Michael L.; Makhnin, Oleg
ABSTRACT: In the Upper Mississippi River basin, after spring fertilizer application, total nitrogen concentration [TN] in streams drops by 73% from June to September, consistent with effects of seasonal nutrient loading. We hypothesized that this seasonal variability might be affected by land cover (e.g. wetland, cultivated area extent). To test this hypothesis, we adopted a linear mixed-effects modeling approach including periodic functions. However, inclusion of wetland area was not indicated, suggesting that increased model complexity associated with inclusion of contemporary wetland extent was unjustified. While consideration of cultivated extent in relation to mean annual [TN] was shown to improve performance, no evidence was observed that cultivated extent could enhance explanation of intra-annual [TN]. Improved understanding of cause and effect will require improved spatiotemporal data on nitrogen sources and additional critical field experimentation, which in turn is expected to set the stage for advancement in physically- or process-based modeling of nutrient concentrations.